2019
DOI: 10.21475/ajcs.19.13.06.p1327
|View full text |Cite
|
Sign up to set email alerts
|

Selection for salinity tolerance in an international rice collection at vegetative stage

Abstract: Water and soil salinity as the main abiotic stresses decrease crop yield and restrict the use of agricultural lands. In order to assess salt stress effect on seedling growth of rice and to select more tolerant rice genotypes, a factorial experiment was performed at two levels of NaCl namely non-stress (EC 1.2 dS m −1 ) and salt-stress (EC 10 dS m −1 ) in hydroponics with an international rice collection consisted of 155 varieties. Seven stress tolerance indices including STI, SSI, HM, RDI, SSPI, ATI and TOL we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
1
6
0
1
Order By: Relevance
“…The position of QTL qRFWs6.1 on chromosome 6 (4.58–4.61 Mbp) is similar to the position of q06_02 for leaf area reported by Frouin et al ( 2018 ). The positions of 2 co-located QTLs qRLs6.1 and qRFWs6.3 on chromosome 6 (29.76–30.92 Mbp interval) are comparable to QTL #2098 for relative seminal root length reported by Prasad et al ( 2000 ). Also, the location of QTLs qRLs8.1 on chromosome 8 (0.06–0.12 Mbp interval) co-locates to a08_04 for tiller number reported by Frouin et al ( 2018 ), and the location of QTL qRLs8.2 on the same chromosome (2.33 Mbp) is comparable to QTL #2175 for leaf water content detected by Ul Haq et al (2010).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The position of QTL qRFWs6.1 on chromosome 6 (4.58–4.61 Mbp) is similar to the position of q06_02 for leaf area reported by Frouin et al ( 2018 ). The positions of 2 co-located QTLs qRLs6.1 and qRFWs6.3 on chromosome 6 (29.76–30.92 Mbp interval) are comparable to QTL #2098 for relative seminal root length reported by Prasad et al ( 2000 ). Also, the location of QTLs qRLs8.1 on chromosome 8 (0.06–0.12 Mbp interval) co-locates to a08_04 for tiller number reported by Frouin et al ( 2018 ), and the location of QTL qRLs8.2 on the same chromosome (2.33 Mbp) is comparable to QTL #2175 for leaf water content detected by Ul Haq et al (2010).…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, the expression pattern of several new genes involved in salt tolerance of rice was investigated by real-time PCR in two sensitive (ARC6578 and Shoemed) and one tolerant (Bombilla) rice accessions that were selected based on previous work (Nayyeripasand et al 2019). RNA samples were extracted from 20day-old seedlings treated with NaCl (100 mM) at three times after salt stress (24, 48 and 72 h).…”
Section: Validation Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al (2018) reported that salttolerance levels in rice (O. sativa) were not strongly correlated with rice subgroups, which was confirmed in a maize population the following year (Luo et al, 2019). Tolerance indices do not accurately distinguish cultivars under severe stress (Mardeh et al, 2006;Mohammadi, 2019), but can be used as indicators for high-yielding, salt-tolerant lines in stress, and non-stress environments or for traits like germination (Nayyeripasand et al, 2019;Sedri et al, 2019).…”
Section: Salt Stress Significantly Inhibited Seed Germinationmentioning
confidence: 98%
“…Traits with low rates of variation are not suitable for selecting tolerant barley genotypes using tolerance indices under stress (Jamshidi and Javanmard, 2017). Nayyeripasand et al (2019) reported a positive correlation among stress tolerance indices, including STI, SSI, and TOL, but not in the subgroups. Yu et al (2018) reported that salttolerance levels in rice (O. sativa) were not strongly correlated with rice subgroups, which was confirmed in a maize population the following year (Luo et al, 2019).…”
Section: Salt Stress Significantly Inhibited Seed Germinationmentioning
confidence: 99%